In situ grown nickel nanoparticles in a calixarene nanoreactor on a graphene-MoS2 support for efficient water electrolysis - Waghmode, Babasaheb J.; Bhange, Siddheshwar N.; Unni, SreeKuttan M.; Patil, Kashinath R.; Malkhede, Dipalee D. (Sustainable Energy & Fuels, 2017)
Electrochemical production of hydrogen, facilitated in electrolysers, holds great promise for energy storage and solar fuel production. Catalysis of the oxygen evolution reaction (OER) is a bottleneck of this process. However, the sluggish OER kinetics and the utilization of precious metal catalysts are key obstacles in the broad deployment of this energy technology. We report the preparation and use of an inexpensive GrMoS(2)SC(8)Ni nanocomposite material as a highly effective OER catalyst in an alkaline electrolyte. Experimental investigations have shown that improvements can be realized in the catalytic performance of Ni metal if it is a component of the composite material. We propose an explanation for these enhancements based on a hydrogen acceptor concept. This concept comprises the stabilization of an *-OOH intermediate, which effectively lowers the potential needed for breaking bonds on the surface. Herein, an inexpensive immobilized SC8 layer was used as the nanoreactor to synthesize metallic Ni nanoparticles (NPs) through an in situ redox process. The process was applied to form immobilized NPs on flat and curved 2D surfaces. The outstanding OER performance of Ni NPs could be attributed to their large surface area, efficient mass and charge transport, and high structural stability arising from the unique SC8 cage structure, built on the GrMoS(2) substrate. The GrMoS(2)SC(8)Ni nanocomposite shows the highest activity, exhibiting a 214 mV overpotential at 10 mA cm(-2) (equivalent to 10% efficiency of solarto-fuel conversion) and a Tafel slope of 31 mV dec(-1) in 1 M KOH solution. It further demonstrates high stability as there is no apparent OER activity loss (based on a chronoamperometry test) or particle aggregation (based on SEM image observation) after a 10 h anodization test. The facile preparation method and high efficiency and durability enable this electrocatalyst to be a promising candidate for future large-scale applications in water splitting. Thus, this work opens a new avenue toward the development of highly efficient, inexpensive OER catalysts.